PENGARUH PENGGUNAAN BUKU SAKU “TANGGAP TANGKAS TANGGUH” TERHADAP KESIAPSIAGAAN WARGA SEKOLAH DALAM MENGHADAPI GEMPA BUMI - Ragil Bunga Setianingsih; Aris Munandar; Asma Irma Setianingsih (Jurnal Manajemen Bencana (JMB), 2023)
This study aims to determine the effect of using the "Tanggap Tangkas Tangguh" Pocket Book on School Citizen Preparedness in Facing Earthquake Disasters at SMA Negeri 51 Jakarta. This study used a quantitative method with a One group Pre-Test Post-Test research design. The population in this study were all school residents with a total of 926 people. The sampling technique in this study used probability sampling technique, namely proportionate random sampling with the sample used consisting of 100 people with details of 93 students, 5 educators, and 2 education staff. The data obtained came from the scores of the Pre-Test and Post-Test questions on earthquake preparedness, while the data were analyzed using the Paired Sample T-Test equality test. This study shows the results that the use of the "Tanggap, Tangkas, Tangguh" pocket book increases the average preparedness of school residents from 24.25 to 31.80 in students and from 21.43 to 28.43 in educators and education personnel. So it can be concluded that there is an effect of using the "Tanggap, Tangkas, Tangguh" booklet on the preparedness of school community in facing earthquake disaster at SMAN 51 Jakarta.